2019
DOI: 10.1021/jacs.9b06923
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Symmetry: Engineering Single-Chain Dimeric Streptavidin as Host for Artificial Metalloenzymes

Abstract: The biotin–streptavidin technology has been extensively exploited to engineer artificial metalloenzymes (ArMs) that catalyze a dozen different reactions. Despite its versatility, the homotetrameric nature of streptavidin (Sav) and the noncooperative binding of biotinylated cofactors impose two limitations on the genetic optimization of ArMs: (i) point mutations are reflected in all four subunits of Sav, and (ii) the noncooperative binding of biotinylated cofactors to Sav may lead to an erosion in the catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 66 publications
1
41
0
Order By: Relevance
“…14a). Hence, residues from both monomers can interact with the catalyst and substrates, 141 and the docking studies revealed that the S112Y mutation from each monomer, namely S112Y A and S112Y B , is essential to the catalysis by ligand 14.…”
Section: Non-covalent Supramolecular Systemsmentioning
confidence: 99%
“…14a). Hence, residues from both monomers can interact with the catalyst and substrates, 141 and the docking studies revealed that the S112Y mutation from each monomer, namely S112Y A and S112Y B , is essential to the catalysis by ligand 14.…”
Section: Non-covalent Supramolecular Systemsmentioning
confidence: 99%
“…Most monovalent scdSav artIREDs were found to outperform their equivalent divalent scd artIREDs, among them, the best variants for producing (R)-3b (91% e.e., 100% conversion, 0.05 mol% catalyst loading), (R)-4b (96% e.e., 99% conversion, 0.05 mol% catalyst loading) and (S)-5b (91% e.e., 98% conversion, 0.5 mol% catalyst loading). 51 Directed evolution. Although other design strategies had initially had some success, it has proved challenging to predict the subtle effects of protein structure and bonding on enantioselectivity.…”
Section: Rsc Chemical Biology Reviewmentioning
confidence: 99%
“…For iridium-based ArMs, the majority of literature studies thus far have extensively focused on their use as artificial transfer hydrogenases (ATHase). [113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132] In these works, asymmetric transfer hydrogenation has been shown possible for a number of substrates that include imines, enones, ketones, and for NAD + reduction. One intriguing example of an ATHase that has been used with biological systems relies on a cell-surface display system that shuttles streptavidin into the E. coli periplasm ( Figure 5A).…”
Section: New-to-nature Reactions Of Armsmentioning
confidence: 99%